Glycerol derived mesopore-enriched hierarchically carbon nanosheets as the cathode for ultrafast zinc ion hybrid supercapacitor applications. (20th May 2021) - Wang, Dewei; Pan, Zhongmou; Chen, Guoxian; Lu, Zeming
Highlights: A zinc acetate-assisted pyrolysis strategy has been developed for the synthesis of porous carbons from glycerol. The content of zinc acetate has a profound influence on the textural parameters of the resulting samples. Carbon formation mechanism and the morphology evolution process has been proposed. The obtained nanocarbons exhibit large surface area and ultra-high mesopore content. Aqueous zinc ion hybrid supercapacitors with superior rate capability have been realized. Abstract: Direct transformation of small molecular organic solvents (SMOSs) into functional carbon materials have received paramount interests in recent years, although it remains a huge challenge. Herein, we demonstrate an efficient zinc acetate-assisted pyrolysis strategy to direct transformation of glycerol into mesopore‐enriched hierarchically carbon nanosheets (MEHCs). We found that the initial formed glycerin zinc would be one of the major ways in immobilization of glycerol from volatilization as well as determining the morphology of the resulting carbons. By optimizing the amount of zinc acetate, MEHCs with large specific surface area (1666.8 m 2 g −1 ), ultra-high mesopore content (Smeso = 1488.7 m 2 g −1 ) and total pore volume (2.42 cm 3 g −1 ) were obtained. Benefiting from the unique structure features, the as-assembled aqueous zinc ion hybrid supercapacitors with the as-prepared MEHCs as the cathodes can deliver a specific capacity of 132.9 mAh g −1, and rate capability up to 49.1% at 50 Ag −1, which is one of the largest values in comparison with the previously reported values. Such promising results indicate that the newly developed strategy would offer a valuable avenue for the production of functional nanocarbon materials from SMOSs for electrochemical energy storage applications. Graphical abstract: Image, graphical abstract